2023
DOI: 10.1038/s41598-023-48480-z
|View full text |Cite
|
Sign up to set email alerts
|

Discharge protocol in acute pancreatitis: an international survey and cohort analysis

Rita Nagy,
Klementina Ocskay,
Zoltán Sipos
et al.

Abstract: There are several overlapping clinical practice guidelines in acute pancreatitis (AP), however, none of them contains suggestions on patient discharge. The Hungarian Pancreatic Study Group (HPSG) has recently developed a laboratory data and symptom-based discharge protocol which needs to be validated. (1) A survey was conducted involving all members of the International Association of Pancreatology (IAP) to understand the characteristics of international discharge protocols. (2) We investigated the safety and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The latest study conducted among adults with AP shows that patients discharged based on protocols have a significantly shorter median LOH (7 days [5;10] vs. 8 days [5;12]; p < 0.001], and a lower rate of readmission due to recurrent AP episodes (p = 0.005). 36 In our study, the protocol did not specify the criteria for discharge from the hospital and the time differed between centres based on their experience and internal arrangements.…”
Section: Discussionmentioning
confidence: 97%
“…The latest study conducted among adults with AP shows that patients discharged based on protocols have a significantly shorter median LOH (7 days [5;10] vs. 8 days [5;12]; p < 0.001], and a lower rate of readmission due to recurrent AP episodes (p = 0.005). 36 In our study, the protocol did not specify the criteria for discharge from the hospital and the time differed between centres based on their experience and internal arrangements.…”
Section: Discussionmentioning
confidence: 97%
“…The median cost of readmissions was also higher compared to index hospitalizations. In a recent international survey, Nagy et al [ 62 ] revealed the efficacy of the AP discharge protocol in significantly reducing median LOS and recurrent AP-related readmission rates. Our findings could enable pancreatologists to devise novel discharge protocols that include index admission APFC and assess their impact in future research.…”
Section: Discussionmentioning
confidence: 99%